2021
DOI: 10.1039/d0ra10945b
|View full text |Cite
|
Sign up to set email alerts
|

Efficient photocatalytic degradation of dyes using photo-deposited Ag nanoparticles on ZnO structures: simple morphological control of ZnO

Abstract: Morphology control of ZnO structures were fabricated by hydrothermal method with simple adjustments of NaOH concentration and Ag–ZnO composite showed superior photoactivity and recyclability for the degradation of MO and RhB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 63 publications
0
18
0
Order By: Relevance
“…Due to the advantages of the photocatalytic process, a review paper was recently published on the selection of suitable methods for the preparation of photocatalysts to obtain the desired size of ZnO nanostructures, which were attempted to improve their photoreaction. Undoubtedly, ZnO has aroused worldwide research interest due to its low toxicity, biocompatibility, and a variety of morphologies. Morphologically diverse ZnO nanostructures allow a wide area of application due to the fact that the behavior of ZnO is related to their morphology. Wiesmann et al reported a significant role of ZnO nanoparticles (NPs) as innovative agents for medical applications for therapeutic purposes in cancer medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the advantages of the photocatalytic process, a review paper was recently published on the selection of suitable methods for the preparation of photocatalysts to obtain the desired size of ZnO nanostructures, which were attempted to improve their photoreaction. Undoubtedly, ZnO has aroused worldwide research interest due to its low toxicity, biocompatibility, and a variety of morphologies. Morphologically diverse ZnO nanostructures allow a wide area of application due to the fact that the behavior of ZnO is related to their morphology. Wiesmann et al reported a significant role of ZnO nanoparticles (NPs) as innovative agents for medical applications for therapeutic purposes in cancer medicine.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Rania et.al reported the preparation of the ZnO nanoparticles by co-precipitation method for solar-driven photodegradation of Congo red dye [18], Mohd Farhan Khan. et.al reported by sol-gel method for antimicrobial activities [19], Hyeonhan Lim et.al reported by hydrothermal method photodegradation studies [20], Mosalagae. et.al reported by ultrasonic spray pyrolysis method [21], Anh Thi Le.et.al reported by solid precipitation method for removal of heavy metal ions [22], Yan Xiu Liu et.al reported microwave-assisted zinc oxide nanoparticles for photodegradation of CTMAB [23], Dapeng Wu et.al. prepared by the solvothermal method for dye-sensitized solar cells [24], Jen-Chieh Lin et.al synthesized by microemulsion technique for dye-sensitized solar cells [25], Raghu and Ram synthesized by supercritical water method [26] and Giri.…”
Section: Introductionmentioning
confidence: 99%
“…Organic contaminants, which are mainly employed in processing products such as fabrics, cosmetics, leather, plastic, ceramics, paper, ink-jet printing, pharmaceuticals, etc. [ 2 , 3 , 4 ], are due to the discharge of organic dyes through industrial wastewater. In aquatic life, different pollutants were identified, including textile dyes, surfactants, insecticides, pesticides and heavy metals [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Such defects generate mid-bandgap energy levels which are reported to increase carrier trapping leading to rapid non-radiative recombination of the electron–hole pairs within the semiconducting materials. Although doping can be used to enhance the general efficiency of the photocatalyst, many contributions to a changing performance have to be considered, such as preparation method [ 23 ], particle morphology [ 12 , 24 ], surface properties [ 25 , 26 ] and defects [ 27 ], dopant concentration [ 2 ] as well as the charge transfer dynamics of the discoloration process [ 28 ].…”
Section: Introductionmentioning
confidence: 99%